Whoosh! : 250 ways to get motion into your drawings - Gomes Cabral, Carlo (Hauppauge, New York : Barron's, 2016)
"The best cartoonists jam-pack their work with action that moves the story along. So how do you capture this kind of motion in your work? Whoosh! 250 Ways to Get Motion into Your Drawings can help. Cartoonist and illustrator Carlos Gomes Cabral shares his tips and tricks to help you create attention-grabbing drawings that practically leap off the pages."--provided from Amazon.com.
1. Stuff you need to know -- The human head -- Useful textures -- Working in layers -- Basic types of movement -- Demystifying light -- Easy perspective -- The basic figure -- Laura Braga -- Dennis Jones -- 2. Humanize your characters -- Mastering expressions -- Body language -- Designing characters -- Stylization -- How different characters move -- Brittany Myers -- Jonathan Hill -- 3. Movement and life -- Foreshortening -- Flexibility and exaggeration -- Weight -- Dynamic hands -- Powerful action -- Animal movement / Donna Lee -- Elisa Ferrari -- Louis Decrevel -- 4. Storytelling -- Direct your characters -- Composition rules -- Powering your scenes -- Props and staging / Mark A. Robinson -- Mark A. Robinson -- Jason Chatfield.
"A Quarto book"--Title page verso.
Includes index.
Keywords: Cartoon characters; Comic books, strips, etc. -- Technique -- Japan; Cartooning -- Technique; Architectural drawing -- Technique